Analisis Kesulitan Guru Mata Pelajaran dalam Implementasi Kurikulum Merdeka Belajar di Kelas VIII SMP Negeri 2 Hiliduho T.A 2024/2025: Penelitian - Jefri Memori Zebua; Wahyutra Adilman Telaumbanua; Eka Septianti Laoli; Arianto Lahagu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The successful implementation of a curriculum is determined by teachers’ understanding of curriculum content, their readiness in planning and implementing instruction, as well as the availability of training and school resources. In the context of the Merdeka Curriculum, teachers are required to be more autonomous in designing learning activities, implementing differentiated instruction, and carrying out the Pancasila Student Profile Strengthening Project (P5). This study aims to describe teachers’ difficulties in understanding the principles and basic concepts of the Merdeka Curriculum, analyze the obstacles faced by teachers in designing learning activities using the Merdeka Curriculum approach, identify the challenges encountered in implementing differentiated learning and the P5 project, explain teachers’ difficulties in conducting formative and summative assessments based on learning outcomes, and reveal the role of facilities, infrastructure, and the school environment in supporting or hindering the implementation of the Merdeka Curriculum. This study employs a descriptive research method with a qualitative approach. Data were collected through observation, interviews, and documentation. Based on the findings, the difficulties experienced by subject teachers in implementing the Merdeka Curriculum include limited understanding of curriculum concepts, challenges in planning and implementing learning activities, suboptimal assessment practices, and external factors that influence curriculum implementation.